Study on mechanical characteristics of mixed heterogeneous coastal plastic waste - Norazimah, Harun (2012)
Coastal plastic pollution is a common problem in many coastal regions in Malaysia. Arising from environmental concern and at the same time supporting waste to wealth program, the best way to overcome coastal plastic pollution is by recycling. However, due to photo degradation and nature of the surroundings, the characteristics of coastal plastic waste are differ from land plastic waste that drives for further research in determining the characteristics of coastal plastic waste and discovering its potential value. The objectives of this study are to improve the characteristics of mechanical properties of coastal plastic waste by heterogeneous recycling, to compare the mechanical properties of heterogeneous coastal plastic waste with the commercial plastic and to study the potential value of heterogeneous coastal plastic waste. Polypropylene (PP) and Polyethylene terephthalate (PET), two types of plastic waste which are highly abundant at the coastal region for its great consuming in food and beverages packaging and containers are used as sample. Samples are collected, cleaned and sorted manually according to the types and crushed into small flakes. PP and PET are mixed by volume composition of 0%, 3%, 5%, 7% and 10% of PET before undergo extrusion process. Under extrusion process, the plastic is extruded to strands and then pelletized to produce a single-polymer plastic. Then, plastic is moulded into testing specimen according to standard measurement, ASTM D638-05 and tested in term of its mechanical properties- tensile strength, elongation at break and elastic modulus- by using Universal Testing Machine. From analysis of obtained result, the mechanical properties of mixed heterogeneous coastal plastic waste are poor compared to homogeneous recycling except for elastic modulus. However, at 7% composition of recycle PET, it shows the optimum mixing ratio which gives better of mechanical properties. Homogeneous recycled plastic has the close and almost similar mechanical properties as the commercial plastic and have the potential to be utilized in some application as in producing household items. Varying the mechanical testing and blending polymers with plastic additives can be applied in further research for improvement of mechanical characteristics of recycled materials.